2015
DOI: 10.1177/1098611115604449
|View full text |Cite
|
Sign up to set email alerts
|

Departmental Professionalism and Its Impact on Indicators of Violence in Police–Citizen Encounters

Abstract: Citizens' beliefs that officers are employing unnecessary or excessive levels of force can quickly erode police legitimacy and can lead to severe consequences including loss of life, civil disorder, criminal prosecution, and large civil judgments. Although scholars have devoted more than four decades of research to identifying the correlates of police-citizen violence, relatively little study has focused on the relationship between departmental measures of police professionalism and violent outcomes between ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 88 publications
2
36
0
1
Order By: Relevance
“…Research also finds racial and ethnic minorities (Nix, Campbell, Byers, & Alpert, 2017;Paoline, Gau, & Terrill, 2017, but see Worrall, Bishopp, Zinser, Wheeler, & Phillips, 2018 and members of the lower class are more likely subjected to police force (Alpert, Dunham, & MacDonald, 2004;Terrill & Mastrofski, 2002). Organizational assessments have found agency structure, policies, training programs, and supervisory styles impact officer use of force (Alpert & MacDonald, 2001;Fyfe, 1979;Geller & Scott, 1992;Klinger, 2010;Riksheim & Chermak, 1993;Shjarback & White, 2016), while ecological approaches show how officer behavior may be shaped by the external environment (Jacobs & O'Brien, 1998;D. A. Smith, 1986;Terrill & Reisig, 2003;White, 2003).…”
Section: Factors Influencing Police Use Of Forcementioning
confidence: 99%
“…Research also finds racial and ethnic minorities (Nix, Campbell, Byers, & Alpert, 2017;Paoline, Gau, & Terrill, 2017, but see Worrall, Bishopp, Zinser, Wheeler, & Phillips, 2018 and members of the lower class are more likely subjected to police force (Alpert, Dunham, & MacDonald, 2004;Terrill & Mastrofski, 2002). Organizational assessments have found agency structure, policies, training programs, and supervisory styles impact officer use of force (Alpert & MacDonald, 2001;Fyfe, 1979;Geller & Scott, 1992;Klinger, 2010;Riksheim & Chermak, 1993;Shjarback & White, 2016), while ecological approaches show how officer behavior may be shaped by the external environment (Jacobs & O'Brien, 1998;D. A. Smith, 1986;Terrill & Reisig, 2003;White, 2003).…”
Section: Factors Influencing Police Use Of Forcementioning
confidence: 99%
“…Furthermore, higher proportions of women on the police force are correlated with increased sexual assault reporting and arrests (Meier & Nicholson-Crotty, 2006) and the reporting and clearance of rape cases (Schuck, 2018), whereas the presence of a woman chief of police is correlated with higher domestic violence arrests (Andrews & Miller, 2013). Nevertheless, other research has found no statistically significant differences when examining the link between the representation of women and civilian complaints, assaults against officers, or domestic violence arrests (Eitle, 2005; Shjarback & White, 2015; B. W. Smith & Holmes, 2003; S.…”
Section: Improved Personnel Standardsmentioning
confidence: 93%
“…Doing so would utilize community input and support to mutually design custom-tailored policing strategies and approaches to community problems (Cordner, 2014; Gill et al, 2014). However, while viewed as an organizational philosophy or approach, scholars have empirically evaluated community policing as it pertains to specific programs or features of the COP philosophy such as the utilization or presence of foot patrols, community policing units, community policing plans, among others (see, for example, Barrick, Hickman, & Strom, 2014; Shjarback & White, 2015; B. W. Smith & Holmes, 2014).…”
Section: Building Police–community Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fridell and colleagues (2009) evaluated the impact of a variety of policies and practices, including training hours, dispatch policies, and use of force reviews (among others), on violence against the police. Shjarback and White (2016) also assessed the effects of departmental professionalism, measured via education, hiring standards, and training hours (among others), on violence and complaints against the police (Cao and Huang (2000) used similar measures to predict citizen complaints as well). Other research has also examined the effects of collective bargaining policies on supplemental pay benefits (e.g., hazardous duty, shift differential, education incentive, and merit pay; Briggs et al 2008) and innovation practices (Morabito 2014).…”
Section: Staffing Rigormentioning
confidence: 99%